Phenotypic Convergence in Sea Bass (Dicentrarchus labrax) Escaping From Fish Farms: The Onset of Feralization? - Toledo-Guedes, Kilian; Brito, Alberto; Garcia de Leaniz, Carlos (Frontiers in Marine Science, 2021)
The impact of fish escaping from fish farms may depend on the extent to which escapees adapt to the natural environment, resemble wild conspecifics and become feral. Yet, little is known about the process of feralization in marine fish. We examined phenotypic changes in body shape, body condition and scale growth profiles of sea bass escaping from fish farms in the Canary Islands, and quantified the extent to which escapees had diverged from farmed conspecifics. Most feral sea bass had sizes that overlapped with those of farmed fish, indicating that they had escaped throughout the production cycle. However, 29% of escapees were larger than the maximum size at harvesting, indicating growth in the wild. Analysis of scale growth profiles showed that some escapees had grown in the wild as fast as did in cages, albeit at more variable growth rates. Feral sea bass tended to converge towards a similar body shape, having more streamlined bodies, lower body condition, and lower hepatosomatic indices than fish in cages. Although our study cannot discriminate between phenotypic plasticity and differential mortality of escapees, we interpret phenotypic convergence as the likely result of a period of initial starvation, phenotypic plasticity, and selection against maladapted phenotypes. Our results warn against the risks of rearing sea bass in open-net cages and suggest that sea bass escapees could pose a threat to shallow coastal assemblages, particularly in areas where the species is not naturally found.